Velhice, adoecimento e morte: uma estilística da existência. - Pitanga, Danielle de Andrade (2018)
Old age, through serious illnesses, brings about a constant battle between life and death. The inexorable deterioration of chronic degenerative diseases brings the elderly to a paradox, that is, on the one hand, the threat of annihilation is painful, causing anguish and suffering; on the other hand, it makes them prone to assigning new meanings to their existence, reconsidering their perspectives in order to find reasons to live. The restlessness in face of the unfathomable limits of life, which takes shape with our growing consciousness of mortality itself, requires that the elderly take charge of what ails them. Thus, this work seeks to grasp the modes through which the elderly suffering from chronic degenerative diseases subjectify aging, falling ill and dying. The participants in this study were five old-age individuals suffering from chronic diseases both in and out of hospital facilities. The tools utilized included narrative interviews carried out individually with each participant and a Field Journal. The narratives collected from the elderly and the notes taken in the field sessions were analyzed from the Foucauldian discourse analysis approach. Drawing on Foucault’s writings, the research findings and the successive implications and problems we proposed allowed us to locate old-age in the realm of ethics, aesthetics and stylistics of existence. From this point of view, the participants’ accounts revealed unique elements of subjectivity, of producing their existence and of positioning themselves in face of life and death. Such production of subjectivity is based on an ethical-aesthetical model. The interviewees sought to re-create and re-invent their own aging while seeking to invent their own selves like works of art, devising and assigning life with a particular style. We look at old-age through the angle of the art of living sustained by self-care which also entails the ineluctable caring others.